Fictional politainment: Exposure to international television drama and attitude toward female politicians. (November 2022) - Rasul, Azmat; Shin, Donghee; Beede, Park
We examine the relationship between media use motivations and attitudes toward female politicians by proposing a conceptual model explaining the role of key mediating variables such as identification, narrative transportation, enjoyment, and political self-efficacy in influencing the attitude of the viewers of international TV drama towards female role models (politicians). We investigated the direct and indirect effects between media use motivations and attitudes toward female politicians by recruiting 359 students from two large public universities in the Southeastern United States. The hypothesized model supported the evidence presented in extant scholarship, suggesting that a meaningful entertainment experience could foster an appreciation of the fictional televisual entertainment and positively change attitudes toward female lead characters playing the role of a viable and competent politician. This study resonates with politicians, academics, and activists' concerns that a positive media portrayal could promote the acceptability of female leaders in powerful positions. Our study clarifies the direct and indirect effects between media use motivations and attitudes toward female politicians and the role of crucial mediating variables such as identification, narrative transportation, enjoyment, and political self-efficacy in influencing the attitude of the viewers of international TV drama towards female politicians.